Intellectual Property Rights and Ethics: A Comparison of Philosophical Approaches in Northern and Southern Countries - Kurniawan, I Gede Agus; Samsithawrati, Putu Aras; Disantara, Fradhana Putra; Nutakor, Briggs Samuel Mawunyo; Thuong, Mac Thi Hoai (Universitas Muhammadiyah Purwokerto, 2025)
The philosophical differences between Northern countries, which adopt utilitarian and libertarian perspectives emphasizing strict Intellectual Property Rights (IPR) protection, and Southern countries, which prioritize distributive justice and universal access, create tensions in implementing global IPR policies, particularly concerning important issues such as access to medicines and technology. This research aims to analyze the influence of philosophical approach differences between Northern and Southern countries on Intellectual Property Rights (IPR) policies and implementation, as well as their ethical implications for public access to knowledge and technology. This research employs normative legal research methods with a conceptual approach, analyzing primary, secondary, and tertiary legal materials through literature study, and uses qualitative analysis to interpret the differences in philosophical approaches to IPR policies between Northern and Southern countries along with their ethical implications. The research findings show that philosophical differences between Northern countries, which adopt a utilitarian-libertarian approach with strict IPR protection, and Southern countries, which emphasize distributive justice-collectivism with a more flexible approach, have significant ethical implications for public access to knowledge and technology, as seen in the HIV/AIDS crisis in Africa and access to education, where strict patent policies of Northern countries often hinder developing countries' access to important technology and knowledge, while Southern countries advocate for universal access especially for basic needs such as health and education, creating tension between IPR protection and fulfillment of society's basic needs.